2022
DOI: 10.3389/fphys.2022.953912
|View full text |Cite
|
Sign up to set email alerts
|

Effect of exercise training on nitric oxide and nitrate/nitrite (NOx) production: A systematic review and meta-analysis

Abstract: Background: Exercise and physical activity can improve circulation through various mechanisms, such as the increment of nitric oxide (NO) production, by affecting vascular endothelial nitric oxide synthase, and reducing reactive oxygen species (ROS). Although, theoretically, this mechanism is well known, studies in living subjects have made controversial findings regarding the association of NO production and its metabolites [nitrate/nitrite (NOx)] with physical activity. Hence, this systematic review and meta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…It is responsible for vasodilation regulation and is crucial for arteries’ adaptation to stress or sports activities [ 90 ]. Physical activities generally account for its elevation not only in terms of an acute reaction but also in the form of a long-term outcome of regular exercise [ 91 ]. This is in opposition to the results of our analysis, as only one study observed the elevation of NO [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is responsible for vasodilation regulation and is crucial for arteries’ adaptation to stress or sports activities [ 90 ]. Physical activities generally account for its elevation not only in terms of an acute reaction but also in the form of a long-term outcome of regular exercise [ 91 ]. This is in opposition to the results of our analysis, as only one study observed the elevation of NO [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…[ 43 ] Exercise significantly increased serum nitric oxide levels; meanwhile, endothelial nitric oxide synthase was phosphorylated and activated during exercise. [ 44 , 45 ] Aerobic training and high-intensity interval training reduced central arterial stiffness in humans and rats by increasing the bioavailability of aortic nitric oxide. [ 46 ] A recent study showed that exercise pretreatment significantly induced downregulation of anti-oxidative stress markers, Heme oxygenase-1 and superoxide dismutase 1, expression in the peri-infarct cortex of mice, which may indicate that exercise could alleviate oxidative stress after stroke.…”
Section: Discussionmentioning
confidence: 99%
“…Exercise can enhance the ability of endothelial cells to produce nitric oxide, thereby promoting vasodilation and improving hemodynamics. Studies have shown that exercise can increase the expression and activity of eNOS [7]. The mechanisms mainly involve shear stress (mechanical stimulation of blood vessels by blood flow), changes in calcium ion concentration in endothelial cells, and biochemical signals produced during exercise (such as cytokines and hormones).…”
Section: Nitric Oxide (No) Production and Vasodilationmentioning
confidence: 99%